Family and school cooperation in raising children with Down syndrome - Mirbabayeva Nodiraxon Soliyevna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Down syndrome is a congenital defect disease characterized by the fact that children remain from a different level of growth, both physically and mentally. The article provides information about children with Down syndrome, family and school cooperation in their upbringing.